2016
DOI: 10.1021/acs.langmuir.5b04077
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity as a Tool To Study Biocidal Activity of Sulfobetaine Micelles against Saccharomyces cerevisiae Model Cells

Abstract: Zwitterionic sulfobetaine surfactants are used in pharmaceutical or biomedical applications for the solubilization and delivery of hydrophobic molecules in aqueous medium or in biological environments. In a screening on the biocidal activity of synthetic surfactants on microbial cells, remarkable results have emerged with sulfobetaine amphiphiles. The interaction between eight zwitterionic sulfobetaine amphiphiles and Saccharomyces cerevisiae model cells was therefore analyzed. S. cerevisiae yeast cells were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
1
15
0
3
Order By: Relevance
“…To overcome these challenges,w ee ngineered ap illar- [5]arene-based zwitterionic molecule that possess antibacterial activity and can disrupt biofilms.Z witterionic molecules bearing an equimolar number of homogenously distributed anionic and cationic groups have attracted growing attention as potential antimicrobial agents. [12,13] While previous reports have established that pillar [5]arene derivatives functionalized with different groups on the framework can be used as antibacterial or anti-biofilm formation agents.T herefore,the combination of zwitterionic groups and pillar [5]arene scaffold would endow the new molecule with new biological applications.H erein, we report az witterionic pillar [5]arene,w hich not only shows antibacterial activity against Gram-negative Escherichia coli [E. coli (DH5a)] and Gram-positive Staphylococcus aureus [S. aureus (SH1000)] bacterial strains,b ut also can disrupt established E. coli (DH5a)b iofilms and kill the biofilm-enclosed bacteria without rapid generation of resistance.…”
mentioning
confidence: 99%
“…To overcome these challenges,w ee ngineered ap illar- [5]arene-based zwitterionic molecule that possess antibacterial activity and can disrupt biofilms.Z witterionic molecules bearing an equimolar number of homogenously distributed anionic and cationic groups have attracted growing attention as potential antimicrobial agents. [12,13] While previous reports have established that pillar [5]arene derivatives functionalized with different groups on the framework can be used as antibacterial or anti-biofilm formation agents.T herefore,the combination of zwitterionic groups and pillar [5]arene scaffold would endow the new molecule with new biological applications.H erein, we report az witterionic pillar [5]arene,w hich not only shows antibacterial activity against Gram-negative Escherichia coli [E. coli (DH5a)] and Gram-positive Staphylococcus aureus [S. aureus (SH1000)] bacterial strains,b ut also can disrupt established E. coli (DH5a)b iofilms and kill the biofilm-enclosed bacteria without rapid generation of resistance.…”
mentioning
confidence: 99%
“…As a result, the biocidal activity declined consequently caused by the interaction between surfactant micelles and microbial cells . By means of 13 C NMR analysis, Chevalier and coworkers found that the measured intercharge distance in betaine structure is shorter than the real ‐(CH 2 ) n ‐ linker length (from ‐(CH 2 ) 2 ‐ to ‐(CH 2 ) 7 ‐), indicating the spacer linker coiling occurred which well corresponded with Tiecco's research work . However, Weers et al .…”
Section: Resultsmentioning
confidence: 99%
“…Zum anderen kçnnen diese Nanoaggregate mit der Bakterienzellmembran durch elektrostatische [15] und hydrophobe Wechselwirkungen interagieren, was zur Verformung der Bakterienzellmembran und letztendlich zum Zelltod führt. [13,16] Ermutigt durch die Wirksamkeit von ZW-PAg egenüber planktonischen Bakterienzellen, untersuchten wir als nächstes dessen Potential bakterielle Biofilme zu zerstçren. Verschiedene Stadien von E. coli (DH5a)B iofilmen (1 Tag, 3T age und 5T age) wurden zunächst vorkultiviert [17] und anschließend fürw eitere 24 hm it ZW-PA-Nanoaggregaten inkubiert.…”
Section: Angewandte Chemieunclassified
“…Je länger die Nanoaggregate mit der E. coli Suspension inkubiert wurden, desto stärker war die Fluoreszenz. [13,16] Ermutigt durch die Wirksamkeit von ZW-PAg egenüber planktonischen Bakterienzellen, untersuchten wir als nächstes dessen Potential bakterielle Biofilme zu zerstçren. Darüber hinaus wurden Cryo-TEM-Messungen durchgeführt, um die Wirkung der ZW-PA-Behandlung auf die Zellmorphologie von E. coli (DH5a)z uv isualisieren (Abbildung 2d-i).…”
unclassified
See 1 more Smart Citation